2016
DOI: 10.2147/ijwh.s112768
|View full text |Cite
|
Sign up to set email alerts
|

Primary dysmenorrhea magnitude, associated risk factors, and its effect on academic performance: evidence from female university students in Ethiopia

Abstract: BackgroundPrimary dysmenorrhea (PD) is the most common gynecologic compliant among adolescent females. There is a wide variation in the estimate of PD, which ranges from 50% to 90%, and the disorder is the most common cause of work and school absenteeism in adolescent females.ObjectiveTo assess the prevalence and associated risk factors of PD among female university students and understand its effects on students’ academic performance.MethodsA cross-sectional study was employed in 440 research participants. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
83
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 25 publications
13
83
4
3
Order By: Relevance
“…Furthermore, the present study did not find a statistical significance between dysmenorrhea and a family history of dysmenorrhea. This finding is in line with Al-Jefout et al's study [24], but differs from another study, which found that a family history of dysmenorrhea was significantly associated with dysmenorrhea [6,10,25]. However, more than one quarter of nursing students in the present study reported a family history of dysmenorrhea.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the present study did not find a statistical significance between dysmenorrhea and a family history of dysmenorrhea. This finding is in line with Al-Jefout et al's study [24], but differs from another study, which found that a family history of dysmenorrhea was significantly associated with dysmenorrhea [6,10,25]. However, more than one quarter of nursing students in the present study reported a family history of dysmenorrhea.…”
Section: Discussionsupporting
confidence: 81%
“…Ranges of associated factors for dysmenorrhea have been identified in the literature of Ju et al and show inconclusive results [4]. In general, dysmenorrhea has associations with age, [5] coffee consumption, [6] body mass index (BMI), [7] skipping breakfast, [8] exercise habits, [9] sleep duration, [7] education specialty, [8] physical activity, a young age at menarche, [10] family history of dysmenorrhea, [11,10,6] depression and stress [9]. Despite the identification of this range of associated factors for dysmenorrhea, the research studies shows conflicting results [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that in the current study, menstrual pain inhibited the daily living activities of the majority of the students. This confirmed that dysmenorrhoea pain negatively affected their ability to perform normal daily activities [8,13].…”
Section: Discussionsupporting
confidence: 66%
“…Dysmenorrhea is the most common gynaecological disorder worldwide, with a prevalence ranging from 50% to 90% according to different countries [1][2][3][4]. The pelvic or lower abdominal pain is one of the most common symptoms of dysmenorrhea, which usually lasts for three days from the beginning of menstruation.…”
Section: Introductionmentioning
confidence: 99%